Divergent climate smartness priority setting by practitioners vis-à-vis advisors: implications on inclusivity, one-health achievement, and enabling environment - Mponela, Powell; Damba, Osman Tahidu; Yeboah, Stephen; Tepa-Yotto, Ghislain; Dalaa, Mustapha Alasan; Kizito, Fred (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
By capturing the prioritization of 22 innovations by 71 farmers against those of advisors, this paper examines the level of awareness and contextualized conceptualization of 31 indicators of Climate Smartness Plus (equity, one health and enabling environment). Concordance analysis reveals differences in prioritization among farmers and agricultural advisors: with advisors giving relatively higher ratings as they set broader goals than farmers. We find that farmers give equal priority to productivity, adaptation, and mitigation while advisors overly prioritise productivity